EVALUATION OF RESEARCH GRANT PROGRAMS INSTITUTE FOR RESEARCH AND COMMUNITY SERVICE STAKEMODEL - Eliagus Telaumbanua; Peringatan Harefa; Yulian Purnama, Maulana Arafat Lubis, Nashran Azizan (Adiba Aisha Amira, 2023)
This research aims to evaluate the planning, implementation and results of the research grant program of the Research and Community Service Institute at the Sultan Muhammad Syafiuddin Sambas Islamic Institute. The research method used is a qualitative research method, ethnographic research type, a Stake model program evaluation approach with stages of antecedents, transactions and outcomes. The research subjects were the Head of LPPM, Head of the LPPM Research Center and Grant Participants. Data collection was carried out through interviews, observation and documentation studies. The data analysis techniques used by the Miles and Hubermen model are: data collection, data reduction, data display and conclusions. The research results showed that: 1. The number of participants who took part increased by 50% and the number of participants who passed increased by 250%. It was found that there was still a lack of participation from lecturers and the number of research grant quotas provided by LPPM had not been fulfilled. 2. Program implementation has been 71.43% complete. It was found that each program activity did not comply with the predetermined schedule. 3. Research results in the form of reports and article publications have only reached 28.57%, the other participants have not completed the research with the time allowance of 4 months. 4. There is contingency between input, implementation and results. Because the number of participants who registered did not meet the quota, additional time was given, so the implementation of research activities also experienced a shift so that the research results were completed far from the target time with a gap of 4 months. Overall, the Research Grant Program is very necessary, continued and improved from aspects that are considered dominant.